Assessment of the Influence of Boundary Layer Ingestion (BLI) on the Axial Fan. Issue 1 (May 2021) - Masaki, A; Ogushi, S; Tsuruta, R; Nishiwaki, D; Sato, T; Okai, K; Kazawa, J; Masaki, D; Harada, M
Abstract: Boundary Layer Ingestion (BLI) is a technology which is effective to reduce fuel consumption of future commercial aircrafts. However, the inlet distortion caused by BLI has a negative on the engine performance. This paper investigates the effect of the inlet total pressure distortion on the aerodynamic performance of the fan rotor. Unsteady numerical analysis was conducted on JAXA TechClean Fan with circumferential distortion caused by BLI. As the result, under the high distorted condition, the peak efficiency of the rotor decreases by 0.622 points. It is found that the main factor of the efficiency reduction is tip-wall passage vortex.